Simple Tenses in English and Ngalum (A Contrastive Study) - Ice Kosay (Journal of Education Papua Baru, 2023)
This study is a contrastive analysis between simple tenses in the English language and the Ngalum language. The research aims to make Ngalum language users understand and aware that Ngalum has a tense system like English, thus making it easier for them to learn tenses in English. The method used in this research is classical contrastive analysis, which involves description, juxtaposition, and comparison. The results of this study indicate that both languages have a tense system. In simple tenses, including past, present, and future tenses. Verbs change according to the tense. The function of these verb changes has the same meaning, indicating activities corresponding to events in the past, present, and future. One notable difference is that verbs in English can stand alone as verbs, while in Ngalum, they are bound to the subject. In the English language, subject markers in English verbs are found in simple present. Especially for the third person.  Additionally, sentence structures differ between the two languages, with English following the pattern of Subject +Verb + Object while Ngalum follows Subject + Object + Verb. Even though these two languages are not closely related, they share a similar typology in terms of tense structure.